Guidelines for Maintaining Sustainable Entrepreneurial Centres - Paul Jones (Entrepreneurship Centres, 2017)
Regional differences determine the way entrepreneurship centres should be organised stimulating socio-economic development. Therefore, a general approach to organising entrepreneurship centres cannot be created. In this chapter, the focus is on providing background on important criteria improving the sustainability of entrepreneurship centres, supported by various process questions that can assist such centres to make a dynamic contribution to socio-economic development.